THE MEANING OF THE LYRICS OF THE SONG "YANG TERLUPAKAN" BY IWAN FALS IN THE SEMIOTICS OF FERDINAND DE SAUSSURE - Nuning Indah Pratiwi; Putu Ratna Juwita Sari; Putu Suparna; Dio Komang Ajisaka (Journal of Digital Media Communication, 2023)
Music is a way to convey messages or communicate using sound to people in different ways. Through music, musicians want to convey messages, explain, entertain others, and use lyrics as a means for the writer to express what they want. Lyrics have a message in the form of words or sentences used to create particular imaginations or conditions in the listener. Songs are also often used as a place to sympathize with the reality of what is happening or imaginative stories. One of the most famous musicians in Indonesia is Iwan Fals. He is a singer and songwriter with pop, rock, country, and folk-pop music styles. Amid the development of the Indonesian music industry, through his songs, Iwan Fals raises social issues in Indonesian life and global life from the late 1970s to the present. Iwan Fals tries to penetrate the boundaries of conventional realism by looking for aspects of reality that have never been shown before. Apart from the character of Iwan Fals' songs, which deal with many social phenomena, he also writes songs with romantic or love nuances where each part of the lyrics has a deep meaning, for example, the song "Yang Terlupakan." "Yang Terlupakan" was rated by Rolling Stone Indonesia magazine as the 42nd best Indonesian song out of 150 best Indonesian songs. "Yang Terlupakan" by Iwan Fals has a profound and robust message about regret for one's past and reality. To analyze the meaning of Iwan Fals' song "Yang Terlupakan," the author uses the semiotic theory of Ferdinand De Saussure. Semiotics, according to Saussure, is the study of signs in social life, including what these signs are and what laws govern the formation of signs.